Correlations and coexistence of characteristics describing body posture and feet in young people of both sexes aged 14 to 18 years - Mrozkowiak, Mirosław; Szurmik, Tomasz; Hadlich, Roland (Journal of Education, Health and Sport, 2017)
Introduction. With the multitude of procedures used for assessment of body posture and the lack of a reliable method without any drawbacks, the choice should depend on the aim of examinations. Contemporary diagnostics allows for determination of the most of characteristics of body posture in quantitative terms, thus reflecting the relationships between each other. The available literature in Poland and abroad has often failed to address this problem. The aim of this study was to determine the significance of the correlation between selected characteristics that describe the system of the pelvis, spine and feet in the population of children of both sexes aged 14 to 18. Materials and research tools The examinations conducted in a group of young people aged 14 to 18 years allowed for recording 2,343 observations, including 1,148 girls and 1,195 boys, and values of 121 characteristics that describe body posture and feet across individual age and sex categories. The test stand for evaluation of body posture and feet using the photogrammetric method is composed of a personal computer, software, screen and printer, and projection-reception device with a camera for measurement of selected parameters. Conclusion Detailed analysis of the distribution of significance of correlations in any age range and gender groups demonstrated their incidentalness and accidentalness, which prevented from establishing any patterns and relationships between the characteristics. The coexistence of these characteristics can be only found. Among the characteristics which describe the pelvis-spine system and are most often correlated with feet characteristics at the age of 14 to 17 years are the characteristics of the frontal and sagittal planes, followed by less pronounced characteristics of the transverse plane. The most frequent and strongest correlations and their coexistence with the characteristics in the area of feet occur in the groups of girls aged 18 years and boys aged 15 and 18 years.